An introduction to object-oriented programming with Java - Wu, C. Thomas (McGraw-Hill, 2004)
An Introduction to Object-Oriented Programming with Java provides an accessible and thorough introduction to the basics of programming in java. This much-anticipated revision continues its emphasis on object-oriented programming. Objects are used early so students begin thinking in an object-oriented way, then later Wu teaches students to define their own classes.